Feeding diversity index as complementary information in the assessment of ecological quality status - Gamito, Sofia (2012)
The feeding diversity of macroinvertebrates from the estuary of Mondego was estimated with Shannon–Wiener complementary evenness following the methodology presented in Gamito and Furtado (2009. Ecological Indicators, 9: 1009-1019). Results were compared with those from BAT (Benthic Assessment Tool; Teixeira et al., 2009. Marine Pollution Bulletin, 58: 1477-1786) applied to the same data set, obtained from sampling carried out in 14 estuarine subtidal stations in Spring of 1990, 1992, 1998, 2000 and 2002. The BAT is a multimetric methodology based on three indices, the Shannon-Wiener and Margalef diversity indices, applied in conjunction with AMBI (Marine Biotic Index). To determinate the feeding diversity, each invertebrate was assigned to a feeding group. Six trophic groups were considered: surface deposit feeders, subsurface deposit feeders, herbivores or grazers, suspension feeders and suspension/deposit feeders. The carnivorous, omnivorous and scavengers were all grouped together, forming the sixth group. The results obtained with both tools pointed out, in general, to the same tendencies. However, in few occasions the feeding diversity pointed out to a high or a bad ecological quality condition whereas the BAT indicated a moderate condition. Occasionally, in stations with average species richness, all individuals were assigned to only one to three 2 feeding groups, and the feeding diversity was low. Even if these taxa were included in the first two or three AMBI sensitive groups, with their presence indicating a possible good ecological condition, they all perform the same ecological function, for example, they are all omnivorous. In these cases the trophic functioning of the system is reduced and the lower trophic levels are missing, such as the suspension-feeders and the decomposers or deposit-feeders. On the contrary, a highly diverse trophic assemblage might be found, but composed of taxa assigned to AMBI ecological groups of species indifferent or tolerant to organic enrichment, and of second-order opportunistic species, indicating a moderate ecological condition, while the feeding diversity will be high. The feeding diversity is, therefore, useful as a complementary information index, measuring other aspects of the community organization, which are not required for ecological quality assessment by the WFD, and so not included in metrics such as BAT.